ENTERPRISE ONTOLOGIES IN HEALTHCARE A PRELIMINARY INCEPTION CONTRIBUTION - Mendes, David (2012)
Current trends in Health Informatics revolve strongly around data interchange issues. Awkwardly, this was a nineties problem in major sectors of the (digital) economy that have evolved steadily to the grander problem of interoperability between systems in most of those sectors. This “semantic” interoperability among information systems is nowadays seen as pretty mature subject in most of the organizations being the commercial sector the leading carrier in this bandwagon. In the late years the efforts towards the formal definitions of Enterprise Ontologies have rendered significant breakthroughs in aligning the “image of the enterprise” (virtual enterprise), that is, its organization reflected in their information systems and the knowledge that can be extracted from them, and the real organizations themselves, their processes and outcomes. This is not yet happening in the Health Sub domain of knowledge and in the HealthCare organizations in particular. Here some contributions are presented to bring both worlds together since there is a strong feeling that the scientific, technological, political, standardization and personal motivation have just arrived. point.